2019
DOI: 10.1177/2047487319833283
|View full text |Cite
|
Sign up to set email alerts
|

Body fat estimates from bioelectrical impedance equations in cardiovascular risk assessment: The PREVEND cohort study

Abstract: Aims: To investigate prospectively the association of body fat percentage (BF%) estimates using various equations from bioelectrical impedance analysis (BIA) with cardiovascular events, compared with body mass index (BMI) and waist circumference. Methods and results: We used data of 34 BIA-BF%-equations that were used for estimation of BF% in 6486 (men ¼ 3194, women ¼ 3294) subjects. During a median follow-up of 8.3 years, 510 (7.9%) cardiovascular events (363 in men; 147 in women) occurred. In men, the crude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…In a DXA-based study, the FRS estimated higher 10-yr CVD risk was associated with a combination of low muscle mass and high fat in men but not in women [38]. In the BIA-based PREVEND study BMI and BF% remained independently associated with CV events in both men and women, while WC -in men only, but not in women [38]. In our sample the 10-yr risk according to the FRS was associated only with the WHR, BF% and FFM, which is an ambiguous finding.…”
Section: Association Of Obesity Indices Body Composition and Cv-riskmentioning
confidence: 96%
See 1 more Smart Citation
“…In a DXA-based study, the FRS estimated higher 10-yr CVD risk was associated with a combination of low muscle mass and high fat in men but not in women [38]. In the BIA-based PREVEND study BMI and BF% remained independently associated with CV events in both men and women, while WC -in men only, but not in women [38]. In our sample the 10-yr risk according to the FRS was associated only with the WHR, BF% and FFM, which is an ambiguous finding.…”
Section: Association Of Obesity Indices Body Composition and Cv-riskmentioning
confidence: 96%
“…Another study of FRS in high-risk ethnic groups highlighted the best predictive value of WHR, while the WC was linked best to the arterial stiffness, and BMI was of value in specific subgroups only [37]. In a DXA-based study, the FRS estimated higher 10-yr CVD risk was associated with a combination of low muscle mass and high fat in men but not in women [38]. In the BIA-based PREVEND study BMI and BF% remained independently associated with CV events in both men and women, while WC -in men only, but not in women [38].…”
Section: Association Of Obesity Indices Body Composition and Cv-riskmentioning
confidence: 98%
“…Recently, it was demonstrated that body fat percentage in bioelectrical measurements is independently associated with the risk of future cardiovascular events and that the calculated percentage with the validated predictive equations can be a more predictive measurement in cardiovascular risk assessment than BMI or WC [19]. Our pilot study provides additional evidence about these results using a BIA.…”
Section: Discussionmentioning
confidence: 59%
“…Visceral fat was a strong point to the risk in alterations to the arterial pressure with p≤0,030 to men and p≤0,004 to women, given that it can provoke the release of pro inflammatory cytokines as interleukin 6 (IL-6), tumor necrosis factor (TNF) and adipokines that are able to reduce the NO levels in the vascular system and provoke reactivity, heightening its constriction (ANCHUELO, MARTÍNEZ-LARRAD, et al, 2019, UCHASOVA, GRUZDEVA, et al, 2018. It is, also, a well referred factor to cardiovascular sickening and arterial hypertension in the scientific literature (BYAMBASUKH, EISENGA, et al, 2019, DAVID, GUIMARÃES, et al, 2019, PICHÉ, POIRIER, et al, 2018, RAPHAEL DAVID, LEMOS SILVA, et al, 2018.…”
Section: Discussionmentioning
confidence: 99%